Upaya Peningkatan Pemahaman Tentang Pentingnya Imunisasi Pada Bayi & Balita Di Praktek Mandiri Bidan Sary Rahayu, S.ST Tahun 2024 - Ngaisah Tri Rahayu (Universitas Maritim AMNI Semarang, 2024)
Immunization is a proven tool for controlling and eliminating life-threatening infectious diseases and is estimated to prevent between 2 and 3 million deaths each year. Immunization is one of the most cost-effective health investments, with a proven strategy that is accessible to even the most hard-to-reach and vulnerable populations. (WHO, 2018). According to Law Number 36 of 2009 concerning Health, immunization is an effort to prevent the occurrence of infectious diseases which is one of the priority activities of the Ministry of Health as a concrete form of the government's commitment to achieving Sustainable Development Goals (SDGs), especially to reduce child mortality. (Permenkes, 2017)